Understanding internet use and dependency - Soh, Ch.-H.; Murali, R. (2006)
Since the 1950s, the Uses and Gratifications approach has been widely applied to explaining the use of the media, such as the radio and newspapers. Recently, this framework has also been applied to the Internet, a new media and has helped in the understanding of how the motivations of individuals affect their Internet usage patterns and their consequences.